Marine clade sensitivities to climate change conform across timescales - Reddin, Carl James; Nätscher, Paulina; Kocsis, Ádám; Pörtner, Hans Otto; Kießling, Wolfgang (Nature Climate Change, 2020)
Rapid climate change is postulated to cause marine extinctions, especially among climate-sensitive clades, traits and regions1–6. This premise is based on two hypotheses: (1) known individual physiological sensitivities scale up to macroecological selectivity patterns4,7,8 and (2) ancient hyperthermal events are appropriate models to anticipate ecological winners and losers of anthropogenic climate change9. Yet these hypotheses have largely escaped quantitative appraisal. Here we show that experimental responses of modern marine ectotherms to single and combined climate-related stressors (such as seawater warming, hypoxia and acidification) align with Phanerozoic fossil extinction regimes across clades and functional traits. Of climate-related stressors, the synergistic interaction between warming and hypoxia10, encumbering aerobic metabolism, has the greatest potency as a proximate driver of extinction. All else being equal8, this synergy particularly imperils modern warm-water organisms. Modern–fossil agreement is strongest at intermediate–high extinction intensities and hyperthermal events but may fail at extreme extinction events, perhaps due to rising prominences of, and interactions among, additional biotic and abiotic stressors. According to results from marine ectotherms, clade-based sensitivity of individuals to climate-related stressors scales up from subannual experiments and decadal range-shift response magnitudes11, to extinction selectivity patterns at ancient climate-related stressor events and the Phanerozoic durations of genera.
CRIS-Team Scopus Importer:2020-02-25